Autoimmune pulmonary alveolar proteinosis in children. Issue 1 (21st March 2022) - Griese, Matthias; Panagiotou, Panagiota; Manali, Effrosyni D.; Stahl, Mirjam; Schwerk, Nicolaus; Costa, Vanessa; Douros, Konstantinos; Kallieri, Maria; Urbantat, Ruth Maria; von Bernuth, Horst; Kolilekas, Lykourgos; Morais, Lurdes; et al.
In childhood, a multitude of causes lead to pulmonary alveolar proteinosis (PAP), an excessive surfactant accumulation in the alveolar space, limiting gas exchange. Autoantibodies against granulocyte–macrophage colony-stimulating factor (GM-CSF) causing autoimmune PAP, the principal aetiology in adults, are rare. In this first case series on autoimmune PAP, we detail the presentation and management issues of four children. Whereas three children presented insidiously with progressive dyspnoea, one was acutely sick with suspected pneumonia. During management, one patient was hospitalised with coronavirus disease 2019, noninvasively ventilated, and recovered. All treatment modalities known from adults including whole-lung lavage, augmentation of GM-CSF by inhaled GM-CSF, removal of neutralising antibody by plasmapheresis and interruption of antibody production using rituximab were considered; however, not all options were available at all sites. Inhaled GM-CSF appeared to be a noninvasive and comfortable therapeutic approach. The management with best benefit-to-harm ratio in autoimmune PAP is unknown and specialised physicians must select the least invasive and most effective treatment. To collect this cohort in a rare condition became feasible as patients were submitted to an appropriate registry. To accelerate the authorisation of novel treatments for autoimmune PAP, competent authorities should grant an inclusion of adolescents into trials in adults. In children, management of autoimmune pulmonary alveolar proteinosis is very challenging. We need to consider all treatment options, as the most effective one with the best harm-to-benefit ratio is unknown. https://bit.ly/3IM220D